Tartib Al-ayat Wa Al-suwar : Kajian Pemikiran Imam Al-Zarqani - Arifin, Zaenul; Wathani, Syamsul (Jurnal AlifLam Journal of Islamic Studies and Humanities, 2021)
The Qur'an is a miracle of the Prophet Muhammad SAW which was revealed to him gradually through the intermediary of the angel Gabriel, and certainly not in the form of a manuscript text that can be read and found as it is today. However, in its development the Qur'an went through many phases such as the Qur'an orally, the codification period to the period of perfecting punctuation, diacritics to the composition of the verses and letters. This research departs from the differences of opinion among scholars in responding to the process of collecting the Qur'an to the stage of compiling verses and letters in the Qur'an. -verse Wa Al-suwar and what are the implications of Tarti>bul Al-ayat wa Al-suwar on the authenticity of the Qur'an. So this study aims to answer these two problems. The nature of this research is qualitative and uses the Interpretative-analytical method, namely by collecting the results of the interpretation or opinion of a character by impressing on a theory. The data obtained will be analyzed according to scientific theories with the provisions of analytical guidelines and according to the rules of writing scientific papers. The results of this study indicate that the arrangement of the verses of the Qur'an is already a provision from the Prophet while the arrangement of the letters is partly tauqifi and partly ijtihadi.